Measuring Quality and Quantity of Indian Library and Information Science Research Output - Chauhan, Suresh K.; Mahajan, Preeti (Journal of Information and Knowledge, 2017)
This paper is based on a bibliometric analysis of Library and Information Science (LIS) research publications in India. The data for the period 1951-2010 was extracted from the Science Citation Index (SCI) and grouped into six blocks each covering a period of ten years. Apart from papers, the present study also touched upon production of Ph.Ds in library and information science in India. The average annual growth of Ph.Ds is 31.05% in the total span of sixty years, whereas average annual growth was found to be 26.07% in the same period. Information centres contributed 6% of total LIS research output whereas highest contribution (34%) was made by LIS professionals working in technical institutions. Over 50% papers were of single authorship. The low productivity and quality of research output in library and information science is also discussed.